Report on business attachment with CAI Consultants Pte Ltd. - Kok, Pei Kee. (2009)
This report documents my learning process in the ten weeks' Business Attachment at CAI Consultants Pte Ltd. By using an analogy of a model, it describes my experiences and at the end gives an objective and retrospective view of the training stint itself. Using the "Black Box" or the transformation phase of the input-process-output model, the focus is on the elements causing the transformation.